The Relationship of Posttraumatic Growth to Peritraumatic Reactions and Posttraumatic Stress Symptoms among Sri Lankan University Students - McCaslin, S.E.; De Zoysa, P.; Butler, L.D.; Hart, S; Marmar, C.R.; Metzler, T.J; Koopman, C (My University, 2009)
The relationships of posttraumatic growth to peritraumatic reactions and posttraumatic stress symptoms were examined in 93 Sri Lankan university students who had experienced a traumatic life event. Posttraumatic growth was associated with peritraumatic dissociation and posttraumatic stress symptoms, but was not associated with peritraumatic emotional distress. Results indicated a curvilinear relationship between peritraumatic dissociation and posttraumatic growth and between posttraumatic stress symptoms and posttraumatic growth. In a regression model predicting posttraumatic growth scores, each of the quadratic relationships of peritraumatic dissociation and posttraumatic stress symptoms to posttraumatic growth were statistically significant, and combined accounted for 22% of the variance. Results suggest that moderate levels of peritraumatic dissociation and symptoms are most associated with the greatest levels of growth.